Influence of metal-metal bonds on electron spectra of MoO2 and WO2 - Gulino, A; Parker, S; Jones, F; Egdell, R (1996)
Core and valence level photoemission and electron energy loss (EELs) spectra of MoO2 and WO2 have been measured. Metal-metal bonding in these distorted rutile dioxides splits the metal 4d or 5d conduction band into two components, with a significantly bigger splitting for WO2 than MoO2. The O 2p bandwidth is also found to be bigger for WO2 then MoO2. Plasmon loss peaks below 2 eV show that the effective mass ratios for electrons not involved in σ metal-metal bonding are much greater than unity. The photoemission and EELS data both suggest that metal-metal π bonding is important in these compounds. Comparison between photoemission spectra of WO2 and oxygen-deficient Na0.65WO3-y suggests that structure evident in the bandgap of the latter compound may be associated with metal-metal bonding allowed by oxygen deficiency.